Waste cooking oil as bio asphalt binder : a critical review - Putra Jaya, Ramadhansyah; K. A., Masri; W. N. A., Wan Azahar; N., Mashros; A. H., Norhidayah; M. N., Mohd Warid; M. K. I. M., Satar; H., Yaacob (2019)
The modification of binder with waste cooking oil (WCO) for paving materials indicates the implementation of recycling practice with environmental issues concern, thus improving the proper management of this waste product. This paper presents a critical review of the WCO utilisation as a modifier to enhance binder properties. The review was focuses on the evaluation of WCO in asphalt binder modification and asphaltic concrete mixture. Basically, oil-based modification by using WCO in paving material provides a promising waste material potential in improving the engineering value in terms of rheological and mechanical performance for modified binder and asphalt mixture. It is expected that the addition of this modifier in binder gives superior performance and is comparable with the conventional binder.